Methodological considerations of clinical research with Deaf adults in Kenya - Ngugi, Joyce, Wangari; Basnight-Brown, Dana; Arasa, Josephine (My University, 2021)
Clinical research with adults who are Deaf in Kenya is nascent and with a loose array of methodological considerations detailed by various authors (Kakiri, 2019). Indeed, Deaf clinical research considerations are necessary for viable outcomes. A desk review of Deaf studies found that there are certain global sets of principles on ethical research and clinical practice considerations with Deaf populations. The document analysis method was used in this literature review, revealing the need for modifications to the standard protocol including the use of a visual-spatial language (Kenyan Sign Language) rather than a spoken language (English), as well as coding and procedural variations from the standardized protocol to fully accommodate Deaf culture. The use of Deaf research assistants or/and the researcher’s reflexivity as a Hearing signing researcher are certain key component of field research considerations. Since the Deaf are a marginalized sub-set of the population, paradigmatic as well as methodological considerations are recommended for effective clinical research in Kenya.
Keywords: Clinical research methodology; Deaf adults; Kenya